2020
DOI: 10.3390/agronomy10091227
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Rhythm of Brassica napus L. Influences Contents of Sulfur-Containing Defense Compounds and Occurrence of Vascular Occlusions during an Infection with Verticillium longisporum

Abstract: Reduction in atmospheric sulfur and intensified agriculture have led to sulfur deficiency, often correlated with a higher susceptibility to pathogens. The spread of fungal pathogens, such as the soil-born Verticillium longisporum, was observed. Defense responses of infected plants are linked to sulfur-containing compounds including glucosinolates (GSLs). Some pathogens infect their hosts at specific time periods during the day. To investigate the relation of sulfur-containing metabolites with diurnal effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Remarkably, they showed that infection with V. longisporum also seems to enhance the synthesis of iGSLs in sulfur-deprived B. napus plants; despite the fact that these plants are very deficient in sulfur they managed to synthesize more iGSLs compared to their infected sulfur-sufficient counterparts. This phenomenon highlights the importance of iGSLs in plant defense [188].…”
Section: Glucosinolatesmentioning
confidence: 69%
See 2 more Smart Citations
“…Remarkably, they showed that infection with V. longisporum also seems to enhance the synthesis of iGSLs in sulfur-deprived B. napus plants; despite the fact that these plants are very deficient in sulfur they managed to synthesize more iGSLs compared to their infected sulfur-sufficient counterparts. This phenomenon highlights the importance of iGSLs in plant defense [188].…”
Section: Glucosinolatesmentioning
confidence: 69%
“…Overexpression of BoTGG1 in A. thaliana leads to accelerated stomatal closure and inhibited stomatal reopening during the infection of Pst DC3000 [187]. Later it was described that the host response to Verticilium longisporum infection differs in Brassica napus plants grown in sulfur sufficient vs. deficient conditions [188]. These authors found that infected plants always showed higher contents of sulfur-containing metabolites, such as specific GSLs, in comparison to non-infected plants.…”
Section: Glucosinolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, recent advances provide unambiguous proof supporting rhythmic oscillation of a broad range of specialized compounds related with plant immunity, cell wall integrity and antioxidant capacity (Goodspeed et al 2012(Goodspeed et al , 2013Jander 2012;Atamian & Harmer 2016;Soengas et al 2018aSoengas et al , 2018bLiebelt et al 2019). Consistent with such oscillations, specialized metabolites that mediate plant defence are synchronized with Lepidoptera, aphid and pathogen circadian behaviour in Arabidopsis thaliana and related Brassica crops (Goodspeed et al 2012(Goodspeed et al , 2013Lei et al 2019;Rupp et al 2020). More recently, Doghri et al (2022) revealed that induction of glucosinolates (GSL), major plant defence metabolites in the Brassicaceae, depends on the time during the day at which the stress event (attack) takes place.…”
Section: Introductionmentioning
confidence: 79%
“…Given the effect of the phytohormones SA, JA, and ET on the contents of GSLs; individual and total phenolic compounds; and carotenoid, chlorophyll and, anthocyanin content by affecting their gene regulation of metabolic biosynthesis, it would be expected that phytochemical accumulation is also involved in the response of the plant clock under pathogen infection. Supporting this notion, a recent study seems to indicate the importance of diurnal rhythms in the accumulation of sulfur-containing defense compounds in B. napus, including GSLs, against the fungal pathogen Verticillium longisporum [72]. Therefore, time of the day and circadian rhythms seem to play a role in the functionality of the plant immune system, which may affect the virulence of pathogens and the overall outcome of host-pathogen relationship.…”
Section: Pathogen Infection and The Clockmentioning
confidence: 90%